A Magnetized Dark Energy Type R/W Model with Polytropic Equation of State in Brans-Dicke Theory (Journal of Scientific Research, 2020)
In this paper, we study the spatially homogeneous Robertson-Walker cosmological models with magnetized isotropic dark energy like fluid in the scalar-tensor theory of gravitation proposed by Brans-Dicke. Variable cosmological constant ᴧ and Polytropic equation of state have been used to find exact solutions of the models with volumetric expansion and power-law relation. The Physical and dynamical behaviors of the models have been discussed using some physical quantities like energy density, pressure, and coefficient of bulk viscosity.